Bioproduced Nanoparticles Deliver Multiple Cargoes via Targeted Tumor Therapy In Vivo - Pourali, Parastoo; Neuhöferová, Eva; Dzmitruk, Volha; Svoboda, Milan; Stodůlková, Eva; Flieger, Miroslav; Yahyaei, Behrooz; Benson, Veronika (ACS omega, 2024)
This study recognized biologically produced gold nanoparticles (AuNPs) as multiple cargo carriers with a perspective of drug delivery into specialized tumor cells in vivo. Paclitaxel (PTX), transferrin, and antimiR-135b were conjugated with AuNPs and their uptake by mouse tumor cells in an induced breast cancer model was investigated. Each of the above-mentioned molecules was conjugated to the AuNPs separately as well as simultaneously, loading efficiency of each cargo was assessed, and performance of the final product (FP) was judged. After tumor induction in BALB/c mice, sub-IC50 doses of FP as well as control AuNPs, PTX, and phosphate buffered saline were administered in vivo. Round AuNPs were prepared using Fusarium oxysporum and exhibited a size of 13 ± 1.3 nm and a zeta potential of -35.8 ± 1.3 mV. The cytotoxicity of individual conjugates and FP were tested by MTT assay in breast tumor cells 4T1 and nontumor fibroblasts NIH/3T3 cells. The conjugation of individual molecules with AuNPs was confirmed, and FP (size of 54 ± 14 nm and zeta potential of -31.9 ± 2.08 mV) showed higher 4T1-specific toxicity in vitro when compared to control conjugates. After in vivo application of the FP, transmission electron microscopy analyses proved the presence of AuNPs in the tumor cells. Hematoxylin and eosin staining of the tumor tissue revealed that the FP group exhibited the highest amounts of inflammatory, necrotic, and apoptotic cells in contrast to the control groups. Finally, qPCR results showed that FP could transfect and suppress miR-135b expression in vivo, confirming the tumor-targeting properties of FP. The capacity of biologically produced gold nanoparticles to conjugate with multiple decorative molecules while retaining their stability and effective intracellular uptake makes them a promising alternative strategy superior to current drug carriers.